Functional redundancy of air exchange processes in technological premises for poultry keeping - Rotova Victoria; Asmankin Evgeny; Ushakov Yuriy; Ivanov Pavel; Neufeld Elena; Rezanov Aleksandr (BIO Web of Conferences, 2024)
The article focuses on the problem associated with emergency power outages at poultry farms. Poultry farming is one of the key branches of agriculture underlying the implementation of the country’s food security doctrine. The trouble-free operation of the technological equipment of poultry workshops is an important and essential condition for improving the productivity and health of poultry. The article presents a method for calculating the multiplicity of air exchange, which makes it possible to determine the optimal parameters of natural ventilation to stabilize microclimatic conditions in a poultry shop in the event of an emergency in the power supply system. The analysis of infrared thermography of the poultry housing confirms the presence of thermally stressed zones and the unevenness of their distribution, which is a prerequisite for creating a model for leveling temperature fields to a physiologically comfortable level for poultry. The article proposes to consider the issue of introducing refrigeration units into the production cycle as a method of solving the issue of livestock safety if it is necessary to transfer the ventilation system to a free-convection mode. The arguments put forward in the article are focused on the impossibility of the bird’s vital activity during the transitional and warm periods, even with a short-term shutdown of the ventilation system. The creation of a temperature difference will provide a backup air exchange for the period of repair work. The analysis of electricity consumption at a poultry enterprise by month allows us to put forward a proposal to redistribute part of it to the cold storage process. The preliminary calculations carried out confirm the sufficiency of the part of the electricity allocated for the implementation of air-conditioned air exchange, with the “tunnel” type ventilation used.